Review: Health Management in Disasters with Focusing on Rehabilitation - Hamid Reza Khankeh; Masoud Fallahi; Maryam Ranjbar; Fazlollah Ahmadi (University of Social Welfare and Rehabilitation Sciences, 2008)
Disasters should never be considered as routine. Disasters of any kind-natural or manmade-clearly disrupt the normal functioning of any community and frequently overwhelm both personal and community resources. In the post-disaster context, following the initial shock of the disaster, returning lives and livelihoods to normalcy becomes a primary concern of the affected communities and nations. Traditionally, this has been known as the recovery and rehabilitation phase, where "normalcy" refers to the return of the community to the state it was in prior to the disaster event. Rehabilitation is this process of returning the community to "normal" that may extend for many years and involves the physical, social and economic components of the community. Disasters can take on a life of their own, therefore being prepared is the single most effective way to improve outcomes. Proper pre-event planning and providing mechanisms for resource coordination are critical which will be resulted a successful response. It should focus on increasing the participation of civil authorities in order to reestablish local authorities. In order to develop safer communities with fewer deaths, physical injuries, and psycho-social trauma following disasters, health systems must be capable of providing a coordinated response during disasters and of delivering effective mitigation and preparedness programs before disaster impact. The health sector has a vested interest and a key role in this process. In addition, prior to the occurrence of disasters, national, provincial, and local planning should be blueprinted by managers. The public must be educated regarding the importance of individual and family preparation for disaster